2020
DOI: 10.1091/mbc.e18-06-0399
|View full text |Cite
|
Sign up to set email alerts
|

Cutting off ciliary protein import: intraflagellar transport after dendritic femtosecond-laser ablation

Abstract: Femtosecond-laser ablation is used in combination with fluorescence microscopy to study how intraflagellar transport in Caenorhabditis elegans is affected by cutting off supply via the dendrite. It is found that IFT reacts in a remarkable, multistep response, allowing rapid adaptation to the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In C. elegans chemosensory cilia, fluorescence recovery after photobleaching experiments and modelling have shown that new tubulin, transported by IFT is incorporated in the axoneme at the ciliary tip and at the end of the proximal segment, where the B-tubules end [ 48 ]. A study employing dendritic laser ablation to block the supply of new material into cilia showed that IFT components redistribute after ablation to the base, followed by shortening of the axoneme [ 149 ]. More recently, similar behavior was observed in response to the chemical repellents the chemosensory cilia sense [ 32 ].…”
Section: Ift Regulation From the Perspective Of The Motorsmentioning
confidence: 99%
“…In C. elegans chemosensory cilia, fluorescence recovery after photobleaching experiments and modelling have shown that new tubulin, transported by IFT is incorporated in the axoneme at the ciliary tip and at the end of the proximal segment, where the B-tubules end [ 48 ]. A study employing dendritic laser ablation to block the supply of new material into cilia showed that IFT components redistribute after ablation to the base, followed by shortening of the axoneme [ 149 ]. More recently, similar behavior was observed in response to the chemical repellents the chemosensory cilia sense [ 32 ].…”
Section: Ift Regulation From the Perspective Of The Motorsmentioning
confidence: 99%
“…Rapid redistribution of IFT dynein and tubulin away from the DS is reminiscent of the laser ablation and azide dosing experiments we have performed before (Mijalkovic et al, 2020). Here it was shown that ablation of the phasmid chemosensory neurons at the dendrite (a couple of micrometers before the start of the cilium), resulted in the activation of retrograde IFT, leading to a redistribution of IFT components out of the DS towards the base on a time scale similar to the SDS-addition experiments presented here.…”
Section: Resultsmentioning
confidence: 79%
“…Remarkably, the shortening appears to stop at the end of the PS, where the axoneme consists of microtubule doublets. In a previous study, femtosecondlaser ablation of the phasmid-neuron dendrites was shown to also cause the collapse of the DS, but not the PS, suggesting that the PS, consisting of microtubule doublets, is more stable than the DS, which consists of microtubule singlets (Mijalkovic et al, 2020). In contrast to IFT dynein, part of the tubulin appears to leave the cilium, as is evident from the increased TBB-4 fluorescence in the dendrite (Figure 1C).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The kymograph indicates that the proximal segments remain intact and no further shortening occurs, presumably because the doublet microtubules in the proximal segment are more stable than the singlet microtubules in the distal segment. 33 The transmembrane protein OCR-2 partially redistributes from the tip into the distal segment (Figure 4D,E). A fraction of OCR-2 remains at the tip, suggesting that the ciliary membrane is not remodeled, e.g.…”
Section: The Ciliary Axoneme Shrinks In Response To Chemical Stimuli ...mentioning
confidence: 99%